Management strategies against frog eye leaf spot pathogen (Cercospora nicotianae) in India - A.R. HUNDEKAR, SHAMARAO JAHAGIRDAR* (Indian Phytopathology, 2010)
Frog eye leaf spot caused by Cercospora nicotianae has become a major threat in recent years accounting to economic loss of 5-50% in India. The field level investigations were taken up with new agro-molecules from 2003 to 2006 at the research farm and large scale demonstrations in farmer’s fields during 2007. The pooled results revealed that spraying of propiconazole @ 0.1% or carbendazim @ 0.05% recorded very low Percent Disease Index (PDI) (23.3 to 23.7). The maximum PDI of 42.9 was recorded in untreated check. Higher yields were obtained in carbendazim or propiconazole sprayed plots with significant superiority over check. Growth parameters like plant height, leaf length and leaf width were also influenced by new molecules accounting to better cured leaf yield and superiority in quality parameters. Net income (Rs.22, 250 per ha) was obtained by carbendazim spray treatment followed by Rs.20,690 per ha with propiconazole. Two sprays with hexaconazole (0.1%) or propiconazole (0.1%) or Carbendazim (0.05%) at 65th and 80th days after transplanting helped in strategic management of frog eye leaf spot with production of excellent quality bidi tobacco in India.